VIOLENCE, IDENTITY, AND RESISTANCE: A DRAMATIC CHARACTERIZATION ANALYSIS OF KICK-ASS 2 - Arvi Farand Arkani; R. Myrna Nur Sakinah (Jurnal Sastra - Studi Ilmiah Sastra, 2025)
This study explores the dramatic characterization in the film Kick-Ass 2 (2013), directed by Jeff Wadlow, by analyzing how characters construct identity, morality, and resistance in a hyper-violent comic-based narrative. Using a literary-critical approach grounded in drama theory and psychological realism, the research focuses on three main figures: Dave Lizewski (Kick-Ass), Mindy Macready (Hit-Girl), and Chris D’Amico (The Motherf***er). The study investigates how their characterization reflects contemporary anxieties about youth, justice, and vigilantism in postmodern cinema. Each character functions not only as a symbolic archetype but also as a dramatic subject undergoing internal conflict and transformation. Through close reading of dialogue, performance, and symbolic action, the paper reveals that Kick-Ass 2 subverts heroic conventions and explores the blurred boundaries between fantasy and trauma. The film, while often dismissed as satire or parody, contains dramatic depth that mirrors real-world issues such as gender identity, moral decay, and the performativity of violence. This analysis contributes to the broader discourse on character development in modern drama and the ethical paradoxes embedded in superhero narratives.